PENGARUH EKUITAS MEREK, DESAIN PRODUK, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PONSEL IPHONE PADA GENERASI MUDA DI KECAMATAN GAJAH, DEMAK - Farida, Dwi Ana; Susilowati, Heni (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
In today's digital era, smartphones have become a symbol of social identity, especially among the younger generation. One interesting phenomenon is the high interest of the younger generation in the iPhone, which is considered an element of a modern lifestyle. This study aims to examine the impact of brand equity, product design, and lifestyle on iPhone purchasing decisions among the younger generation living in Gajah District, Demak. A total of 60 respondents selected using purposive sampling techniques became the sample in this study. Data were collected through questionnaires, and data analysis was carried out using SPSS version 30. The analysis tests applied included instrument tests, classical assumption tests, as well as hypothesis tests and R tests. The results of the study showed that brand equity, product design, and lifestyle have a positive and significant influence on iPhone purchasing decisions among the younger generation in Gajah District, Demak. Companies need to strengthen their brand image, innovate in product design, and adjust their marketing strategies to the dynamic lifestyles of young consumers.